Perceived Organizational Support Sebagai Pemoderasi Hubungan Antara Exploitative Leadership Dengan Employee Green Innovative Behavior (Pada ASN di Dinas Kesehatan Provinsi Sumatera Barat) - Yuliyasti, Rahmi; Fahmy, Rahmi; Syahrul, Laura; ., Yulihasri (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
This research aims to prove and analyze the contribution of perceived organizational support in strengthening the relationship between exploitative leadership and employee green innovativeness behavior. This research was conducted on 121 ASN who work within the West Sumatra Provincial Health Service. The sample collection method used in Lacuna is a census. Data collection was carried out by distributing questionnaires directly, through field observations carried out directly by researchers. The data analysis method used is Moderating Regression Analysis (MRA) which is processed using Stata. Based on the results of hypothesis testing, it was found that perceived organizational support had a positive effect on employee green innovativeness behavior, apart from that it was also found that exploitative leadership had a negative effect on employee green innovativeness behavior. Furthermore, it was also found that perceived organizational support was no able to moderate the relationship between exploitative leadership and employee green innovativeness behavior, in terms of Perceived organizational behavior actually weakens the implementation of exploitative leadership with employee green innovativeness behavior in ASN within the West Sumatra Provincial Health Service.